Larygeotrache oseophageal cleft: a rare entity - Athawale, Hemangi R.; Mane, Shivaji B. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Larygeotrache oseophageal cleft is a rare anomaly in a newborn presenting with respiratory distress and choking with feeding symptoms identical with oesophageal atresia with or without tracheo-oesophageal fistula .It is an abnormal communication of the larynx and the trachea with the oesophagus occurring during fifth to seventh week of gestation as a result of circoid cartilage failing to fuse dorsally. LTOC varies greatly in anatomical extent and clinical severity; more severe forms in which the some or all of the tracheal cartilaginous rings are incomplete are fatal unless corrected surgically. LTOC occurs in less than 1/10,000 to 1/20,000 live births with slightly male predilection and has a autosomal dominant mode of inheritance. Routine chest X-rays and barium oesophagogram are usually not conclusive but bronchoscopy will delineate anatomy of cleft clearly. We present detailed case report of neonate with respiratory distress and choking on feeding and illustrating maneuvers at endoscopy and subsequent individualized surgical management of child.